Analisis Genealogis, Epistemik, dan Praktis atas Penggunaan Jawami‘ al-Kalim di Era Ekosistem Hadis Digital - Ahmad Hadi Pranoto; Faiz Abdul Majid Assharofi; Abid Nurhuda; Yulita Putri; Dewi Sinta; Lady Eka Rahmawati (Sanaamul Quran: Jurnal Wawasan Keislaman, 2025)
This study examines the transformation of the hadith ecosystem in the era of vertical technology through genealogical, epistemological, and practical analyses of the use of Jawami‘ al-Kalim as a digital literacy tool. Changes in the communication landscape from a linear pattern to a vertical pattern, characterised by the dominance of algorithms, accelerated information circulation, and the fragmentation of religious authority, require the repositioning of the hadith treasury in the digital space. Through a qualitative-hermeneutic approach, this study traces the conceptual roots of Jawami‘ al-Kalim as a form of prophetic meaning that combines concise wisdom with ethical depth, then examines how these values can work in a digital architecture rife with misinformation, distortion of authority, and commodification of religiosity. Genealogical analysis shows that the digitisation of hadiths does not merely transfer texts from manuscripts to screens, but also shifts the patterns of epistemic interaction between sanad, matan, and users. Epistemological findings reveal that Jawami‘ al-Kalim can function as a moral filter that guides verification, simplifies messages, and strengthens the ethics of sharing in online spaces. In practical terms, this study formulates a framework for a ‘Digital Hadith Ecosystem’ that places Jawami‘ al-Kalim as the foundation of prophetic wisdom-based digital literacy, as well as a navigation tool for managing algorithmic information flows in a critical, moderate, and responsible manner. Thus, this study reinforces the urgency of integrating hadith science, digital technology, and public ethics in building a more civilised Islamic information civilisation.